Bilingualism: Keeping Spirit Bilingual Program In Local University - Triana Wuri Cahyanti (Dharma Pendidikan, 2017)
English becomes the most essential language in the world. Almost all the people from many different countries around the world use it to communicate. The area of English has always become special interest. It is caused of the importance of English in many scope of human life. In this case, the writer tries to apply bilingual program in teaching speaking and there is conversation in this method, and conversation is part of speaking. It also gives students an opportunity to practice communication in different social contexts and social roles. Bilingual program would seem to be the ideal activity in which students could use their English creatively and it aims to stimulate a opportunity to practice and develop their communication skill.